Colour Oxford Dictionary and Thesaurus - Edited by Livingstone, Charlotte (Oxford, New York Oxford University Press, 2011)
An authoritative and easy-to-use dictionary and thesaurus in one volume containing 45,000 words, phrases, and definitions and 65,000 synonyms.
Keywords: English language -- English language--Synonyms and antonyms